(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Many people have a negative reaction to the word insurance, saying that it is a mandatory, useless thing, why is it necessary? Because in most cases, insurance is mandatory, and people buy insurance policies by paying appropriate amounts to insurance companies. It will show the services provided. Everything can be insured. Simply put, insurance means that we will protect you and provide guaranteed service for a certain amount.